Pengaruh Fortifikasi Kandungan Bahan Organik dari Pupuk Organik Berbahan Baku Feses Sapi Potong dan Feses Ayam Niaga Pedaging Terhadap Bahan Kering Rumput Gajah - Prayogi Sunu; Dewi Nur Anggraeni (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Fortification effects of beef cattle feces with broiler chicken feces on dry matter of elephant grass was carried in the Industrial Area of Superior manure Compost, village district of Mipiran, Padamara, Purbalingga, and Experimental Farm, Faculty of Animal Science of Jenderal Soedirman University and Soil Science Laboratory of the Faculty of Agriculture, Sebelas Maret University Surakarta. This study was aim to determine the effect of commercial broiler chicken feces as the substitute for feces of beef cattle from the aspect of organic matter content and to determine the effect of fertilizer dry matter productions of elephant grass. The materials used were the feces of beef cattle as much as 930 kg, the commercial broiler chicken feces, 270 kg and 2.4 lt EM4. This research method used Completely Randomized Design (CRD) with four treatments (R), namely: R0: 100% beef cattle feces (50 kg), R1: 85% of beef cattle feces (42,5 kg) of commercial broiler chicken feces + 15% (7,5 kg), R2: 70% of beef cattle feces (35 kg) of commercial broiler chicken feces + 30% (15 kg), R3: 55% of beef cattle feces (27,5 kg) of commercial broiler chicken feces + 45 ( 22,5 kg) with six replications.The results showed that the averages of organic matter content of R0, R1, R2, and R3 were 43,071%, 34,075%, 27,815%, and 36,098% respectively. The result of analysis of variance showed that the averages of organic matter that did not use commercial broiler chicken feces (R0) was higher than using commercial broiler chicken feces.The results of analysis showed that administration of compost on the grass did not affect significantly (P>0,05) on fresh production of elephant grass, presumably because it had not decomposed completely. Compost nutrient content was low, therefore, was not sufficient to provide additional nutrients needed by the plants